Model Evaluasi Kinerja Manajemen Berbasis Balanced Scorecard dan Sistem Akuntansi di Era Industri 5.0 - Purwati, Aldina Esty (Universitas Sains dan Teknologi Komputer, 2024)
The demand for real-time performance monitoring in the Industry 5.0 era encourages organizations to adopt integrated approaches to management control systems. This study aims to develop and validate a Balanced Scorecard (BSC)-based performance evaluation model integrated with computerized accounting systems to enhance managerial decision-making quality. The research employs a Research and Development (R&D) approach, following systematic stages of model development including needs analysis, system design, prototype construction, and expert validation. Primary data were obtained from three management accounting experts and two information system practitioners who evaluated the model using five key criteria: accuracy of key performance indicators (KPI), ease of use, indicator relevance, data visualization quality, and implementation feasibility. The findings reveal that all criteria achieved average scores above 4.0 on a five-point scale, indicating a high level of expert consensus and confirming the model’s conceptual validity. The highest scores were recorded for KPI accuracy (4.5) and implementation feasibility (4.4), demonstrating the model’s potential for real-world application. The novelty of this study lies in its integration of BSC metrics with real-time accounting data processing through the R&D approach, resulting in a systematic framework for performance monitoring. Future research is recommended to enhance dashboard interactivity and conduct field implementation testing to measure the model’s impact on decision-making quality.